Investigation of Airflow in A Restaurant to Prevent COVID-19 Transmission Using CFD Software - Azmi, Muhammad Ameer Aiman; Mat Hassan, Nik Normunira; Zuliazura Mohd Salleh (Progress in Engineering Application and Technology, 2022)
According to the World Health Organization (WHO), COVID-19, like other respiratory infectious diseases, is transmitted via droplets and airborne transmission through respiratory activities. The aim of this study is to determine the parameter such as air velocity, temperature and humidity in a restaurant that influence the spreading of COVID-19 with the effectiveness of 2m social distancing in indoor space with an airflow and to study the effect of air flow in spreading of airborne transmitted virus pathogen. A 3D model of the restaurant with an area of 9.2m x 10.5m with ceiling height of 3.2m with two ceiling-cassette air-conditioner units is developed. Both the inlet and outlet of the air-conditioner has a flowrate of 0.14 m3/s and a temperature of 24°C. The simulation is setup with variety of cases consist of manipulated air flowrate, temperature, and inlets and outlets placement. The results produced are Contaminant Removal Effectiveness (CRE), Local Air Quality Index (LAQI), Local Air Change Index (LACI), airflow trajectories and Predicted Mean Vote (PMV). In the manipulated airflow cases, as the airflow rate increase, the CRE value also increase. This is also true for LAQI. A higher airflow rate contributed to a wider spread airflow which can be seen from the airflow trajectories. Meanwhile, as airflow rate increase, the value of LACI decrease. The thermal comfort of the restaurant are within the accepted range of ASHRAE and DOSH standard. Overall, the most effective contaminant removal and the most optimum thermal comfort is the Location 2 case with Contaminant Removal Effectiveness of 0.71 and neutral level of PMV. It is believed that this research will contribute as guidelines to prevent airborne transmitted diseases outbreak.